Peculiarities of Surface Doping with Polyethylene Oxide Thin Film on Porous Silicon - More1, P.S.; Khollam2, Y.B.; Ghuge1, C.S.; Sonone1, R.S. (Asian Journal of Chemistry, 2013)
A miniaturized, non-destructive, non-toxic porous silicon based sensor is investigated as a sensing material to detect leaf moisture at very low moisture concentration. The porous silicon layer (pore size = 10 nm) is obtained by electrochemical etching of p-type silicon wafer. The polyethylene oxide modified porous silicon is obtained by dip-coating method. The difference in sensitivity in green (SF = 55) and yellow (SF = 40) hibiscus leaves indicated that the moisture content in green leaf is more as compared to yellow leaf. In this study, we intend to demonstrate moisture representing the influence of the technological parameters on the porous structure and the device sensitivity.